A Triplex PCR Method for Distinguishing the Wild-Type African Swine Fever Virus From the Deletion Strains by Detecting the Gene Insertion - Huang, Zhao; Xu, Zhiying; Cao, Haoxuan; Zeng, Fanliang; Wang, Heng; Gong, Lang; Zhang, Shengxun; Cao, Sen; Zhang, Guihong; Zheng, Zezhong (Frontiers in Veterinary Science, 2022)
To date, there is no effective vaccine or antiviral therapy available to prevent or treat African swine fever virus (ASFV) infections. ASFV gene deletion strains have been proposed as promising anti-ASFV vaccine candidates. In recent years, most ASFV gene deletion strains worldwide have been recombinant strains expressing EGFP or mCherry as markers. Therefore, in this study, a new triplex real-time PCR (RT-PCR) method was established for the broad and accurate differentiation of ASFV wild-type vs. gene deletion strains. We designed three pairs of primers and probes to target B646L, EGFP, and mCherry, and RT-PCR was used to detect these three genes simultaneously. The detection method prevented non-specific amplification of porcine reproductive and respiratory syndrome virus, porcine epidemic diarrhea virus, circovirus type 2, pseudorabies virus, and classical swine fever virus genes. The minimum copy number of standard plasmid DNA detected using triplex RT-PCR was 9.49, 15.60, and 9.60 copies for B646L, EGFP, and mCherry, respectively. Importantly, of the 1646 samples analyzed in this study, 67 were positive for ASFV, all corresponding to the wild-type virus. Overall, our data show that the triplex RT-PCR method established in this study can specifically identify both ASFV wild-type and gene deletion strains.